What do banks do? What should banks do? - L. Randall Wray (Levy Economics Institute of Bard College, 2010)
Before we can reform the financial system, we need to understand what banks do; or, better, what banks should do. This paper will examine the later work of Hyman Minsky at the Levy Institute, on his project titled 'Reconstituting the United States' Financial Structure.' This led to a number of Levy working papers and also to a draft book manuscript that was left uncompleted at his death in 1996. In this paper I focus on Minsky's papers and manuscripts from 1992 to 1996 and his last major contribution (his Veblen-Commons Award-winning paper). Much of this work was devoted to his thoughts on the role that banks do and should play in the economy. To put it as succinctly as possible, Minsky always insisted that the proper role of the financial system was to promote the 'capital development' of the economy. By this he did not simply mean that banks should finance investment in physical capital. Rather, he was concerned with creating a financial structure that would be conducive to economic development to improve living standards, broadly defined. Central to his argument is the understanding of banking that he developed over his career. Just as the financial system changed (and with it, the capitalist economy), Minsky's views evolved. I will conclude with general recommendations for reform along Minskyan lines.
Keywords: E12; E32; E58; G2; G18; G21; 330; Hyman Minsky; banks and shadow banks; money manager capitalism; finance capital; financial instability hypothesis; global financial crisis; debt deflation theory; Bank; Finanzsektor; Bankensystem; Kapitalismus; Bankenpolitik; Bankenreform